Estudo de membranas porosas de PEI e MCM-41-NH2 na remoção de Cr (III) - Dorst, Diane Damaris (2024)
The present work focuses on the synthesis and characterization of mesoporous materials (MCM-41, MCM-41-NH2) and a mixed polymeric membrane (PEI ) for application in the adsorption of Cr3+ ions from aqueous solutions. The mesoporous materials were synthesized through a hydrothermal route, with MCM-41 being functionalized (MCM-41-NH2) with amino groups using the post-grafting method. Analysis of adsorption/desorption isotherms using BET revealed typical characteristics of mesoporous materials for both MCM-41 and MCM-41-NH2. The average BET pore diameter decreased from 13.07 nm to 4.06 nm upon functionalization. Using the CP-MAS methodology in NMR, three peaks were detected in the 13C spectra (C3 at δ 43 ppm, C2 at δ 23 ppm, and C1 at δ 10 ppm), indicating the presence of the functional group in MCM-41-NH2. The 29Si spectra showed changes in the binding sites, with peaks corresponding to Q2 [SiO2(OH)2] at δ 110 ppm, Q3 [SiO3-OH] at δ 120 ppm, and Q4 [SiO4] at δ 130 ppm in MCM-41. In the spectrum of MCM-41-NH2, the disappearance of the Q2 site and the appearance of peaks corresponding to T2 sites [C-Si(OSi)2OH] at δ 87 ppm and T3 sites [C-Si(OSi)3] at δ 82 ppm were observed, along with the Q3 and Q4 sites at δ 120 ppm and δ 130 ppm, respectively. This confirmed the presence of covalently linked aminopropyl groups. The presence of free silanol groups (Q3 sites) in the MCM-41-NH2 spectrum indicates incomplete functionalization of the mesoporous material with amino groups. Next, an NMR-DT methodology was proposed to determine the adsorption kinetic parameters of Cr3+ ions. A determination coefficient (r²) of 0.9965 was achieved, with a limit of detection (LD) of 1.02 mg·L⁻¹ and a limit of quantification (LQ) of 3.08 mg·L⁻¹. The Langmuir and Freundlich models were used to fit the Cr3+ adsorption data, with maximum adsorption capacity (Qmax) values of 50.98 mg·g⁻¹ and a Freundlich coefficient (Kf) of 9.65 mg·g⁻¹. In comparison, chemically modified sugarcane bagasse showed Qmax = 22.08 mg·g⁻¹ (Langmuir) and Kf = 3.65 mg·g⁻¹ (Freundlich), demonstrating that, under the experimental conditions, MCM-41-NH2 exhibits superior adsorption capacity. Furthermore, the adsorption rate law was determined to be V = k·[MCM-41-NH2]^0.3·[Cr3+]^0.7, with an activation energy (EA) of 588.0 J·mol⁻¹. The mixed polymeric membrane, consisting of PEI , was synthesized via the phase inversion process in proportions of 2.5%, 5.0%, and 10%, and was characterized. The study of the adsorption kinetics of Cr3+ ions did not yield satisfactory results. Without agitation, the membrane did not remove ions from the solution, and under agitation, the PEI membrane (10%) only showed approximately 15% removal. The initial concentration was 291.1 ± 0.7 mg·L⁻¹, and after 12 hours of stirring, the concentration in the solution was 246.3 ± 0.5 mg·L⁻¹. These results highlight the potential of MCM-41-NH2 as a highly efficient material for the removal of Cr3+ ions from aqueous solutions, with NMR-DT emerging as a promising alternative methodology for determining adsorption kinetic parameters.